Simulation Modeling of 140 MW CCGT Quality Indicators Based on DIN-VDI 4661 Standard Using Ebsilon® Professional Software - Mickael Ruben Kaiway; Agustinus Giai; Nourish Christin Griapon; Yohanis Tangke Tosuli; Obet Takke Ranteallo; Samuel Parlindungan Siregar; Yohanis Yulius Wanane; Allo Sarira Pongsapan; Anastasia Sri Werdhani; Pither Palamba; Johni Jonatan Numberi (G-Tech: Jurnal Teknologi Terapan, 2025)
The operational efficiency of mid-capacity (140 MW) Combined Cycle Gas and Steam Power Plants (CCGT) remains underexplored concerning the DIN-VDI 4661 standard, which defines key quality metrics for energy systems. Addressing this gap is crucial for establishing standardized benchmarks to optimize performance and reduce energy losses. Existing studies mainly focus on Combined Cycle Gas Turbine (CCGT) units outside the 100–180 MW range and often do not explicitly follow DIN-VDI 4661, limiting efficiency comparisons and hindering targeted optimizations. This study simulates a 140 MW CCGT using Ebsilon® Professional software, incorporating DIN-VDI 4661 guidelines to assess eight quality indicators, including thermal efficiency, fuel utilization, and power-to-heat ratio. The model integrates gas and steam turbines, heat recovery, and auxiliary components, with input parameters validated against industry data. Energy balance analysis and sensitivity tests identified loss points. Results show a gas turbine thermal efficiency of 31.39%, steam turbine efficiency of 39.59%, and total system efficiency of 48.42%. However, significant energy losses (52% of input energy) were observed, mainly in gas turbines (87,000 kW) and steam turbines (56,000 kW). These findings highlight the need for design optimizations, such as improving heat recovery and turbine efficiency, to meet DIN-VDI 4661 benchmarks.